BseSI, a restriction endonuclease from Bacillus stearothermophilus Jo 10-553, which recognizes the novel hexanucleotide sequence 5'-G(G/T)GC(A/C)C-3'. - Steponaviciene, D (1999)
A new restriction endonuclease Bse SI has been isolated from Bacillus stearothermophilus Jo10-553. Bse SI recognizes a degenerate hexanucleotide sequence 5'-G(G/T)GC(A/C)C-3' and cleaves DNA to produce 3[prime]-protruding tetranucleotide ends.